Standardizing the Growth Conditions for the Production of Hydroponic Fodder Horse Gram - Gunasekaran, S.; Valli, C.; Karunakaran, R.; Gnanaraj, P. Tensingh; Gopi, H. (International Journal of Livestock Research, 2020)
In a fabricated hydroponic fodder production unit biomass yield of hydroponic fodder horse gram in a 2 x 3 factorial design in six replicates was adopted to assess the influence of soaking (8 or 12 hours) and germination time (4 or 8 or 12 hours) of horse gram seeds. Irrespective of the soaking and germination time no significant variation (P < 0.05) was observed on the biomass yield. However, numerically higher biomass yield at 12 hours of soaking and 4 hours of germination was observed. To determine the influence of different seed rate (25, 50, 75, 100, 125 and 150 g / sq.ft) on biomass yield of hydroponic fodder horse gram a study was conducted which revealed the highest biomass yield of 5.28±0.32 kg/ kg of seed at a seed rate of 50 g/sq.ft on 6th day of growth.